ANALISIS PENGEMBANGAN OBYEK WISATA DI DESA SEKERAT KABUPATEN KUTAI TIMUR - Susanto, Fredi; Amransyah, Amransyah; Nelly, Nelly (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2025)
This study aims to analyze tourism potential and develop appropriate development strategies for tourism managers in Sekerat Village, Bengalon District, East Kutai Regency. The research sample was 100 respondents who were taken using convenience or opportunity sampling techniques. Using quantitative research with descriptive analysis that can be seen with four measurements, namely attractions, amenities, accessibility, and ancillary. This study found that tourism in Sekerat Village, Bengalon District, East Kutai Regency has the potential as superior tourism in Sekerat Village, Bengalon District, East Kutai Regency based on an assessment of four aspects (attractions, amenities, accessibility and ancillary) but there are still some weaknesses such as the absence of a halal guarantee. food products, the unavailability transportation to go to tourist attractions, and the lack of optimal cooperation between the government and managers. Based on these results, it can be concluded that it is necessary to improve tourism potential in Sekerat Village, Bengalon District, East Kutai Regency, so that in this study researchers will develop a tourism development strategy in Sekerat Village, Bengalon District, East Kutai Regency